Yearly weight training program for a hockey academy - Pollitt, D. J. (Strength and Conditioning Journal, 2004)
This article describes the types of training programs and yearly plan used at the Banff Hockey Academy. The aim is to provide useful information about a successful junior or prep school type of hockey program that may benefit other coaches in this training genre